COVID-19 and rheumatic diseases: A mini-review - Roseti, Livia; Grigolo, Brunella (Frontiers in Medicine, 2022)
Joint pain and arthralgia can be manifestations of COVID-19, and studies evaluating long COVID symptoms identified the persistence of these disorders. Moreover, some case reports evidenced the development of new inflammatory arthritis in patients with COVID-19, suggesting a possible relation. Viral infections and rheumatic diseases share a documented relationship; they have been associated with genetic and environmental risk factors responsible for some rheumatic diseases. There is crosstalk between viruses and the immune system during the development several of rheumatic diseases. Moreover, infections may participate in the pathogenesis of autoimmune rheumatic diseases and contribute to patient mortality. Therefore, it is crucial to provide a clearer insight into the interaction between viral infections and rheumatic diseases. Here, we provide a mini-review of the current literature, with the aim of shedding light on the relationship between COVID-19 and rheumatic or musculoskeletal diseases, which is still unclear. Specifically, we will examine four aspects: the risk for the rheumatic population of acquiring the virus or developing severe symptoms, the similarities of COVID-19 and arthritis, the possible rheumatic consequence of COVID-19, and COVID-19 prevention in rheumatic patients through vaccination.